Systematic search for a predictor for the clinical observables of alzheimer's disease - Das, Atanu (Journal of Physical Chemistry B, 2021)
One of the prevailing life-threatening incurable neurodegenerative diseases that are presently endangering human society as a whole, and hence, baffling the entire spectrum of the scientific and pharmaceutical world, is Alzheimer's disease (AD). AD is a manifestation of self-assembly of both wild-type (sporadic) and mutated (familial) forms of the amyloid-beta peptide, a proteolytic product of the amyloid precursor protein, where the self-assembly results in the genesis of pathogenic fibrillar aggregates. Currently prevailing diagnostic and hence therapeutic challenges originate from the unavailability of a specific predictor for clinical observables. The continuous emergence of novel pathogenic mutants with unpredictable phenotypes adds immensely to the nonspecific nature of the problem. The current research reports a simple physical parameter, the binding affinity of a protofilament to its protofibril, which predicts the clinical observables of familial AD with astounding accuracy and more importantly, without any adjustable parameters.